Constraining the initial conditions and temperature dependent viscosity with three-particle correlations in Au+Au collisions - STAR Collaboration (Physics Letters B, 2019)
We present three-particle mixed-harmonic correlations 〈cos⁡(mϕa+nϕb−(m+n)ϕc)〉 for harmonics m,n=1−3 for charged particles in sNN=200 GeV Au+Au collisions at RHIC. These measurements provide information on the three-dimensional structure of the initial collision zone and are important for constraining models of a subsequent low-viscosity quark–gluon plasma expansion phase. We investigate correlations between the first, second and third harmonics predicted as a consequence of fluctuations in the initial state. The dependence of the correlations on the pseudorapidity separation between particles show hints of a breaking of longitudinal invariance. We compare our results to a number of state-of-the art hydrodynamic calculations with different initial states and temperature dependent viscosities. These measurements provide important steps towards constraining the temperature dependent viscosity and longitudinal structure of the initial state at RHIC. © 2018 The Author
Keywords: dept.phy; peer-reviewed